Changes in pastoral mobility in a semi-arid montane region of South Africa: The role of policy and legislation. Issue 1 (12th March 2021) - Igshaan Samuels, M; Allsopp, Nicky; Timm Hoffman, M
Abstract : Legislation and policy are key tools used by governments to change the socio-economic and political landscape of agrarian systems with consequences for mobile pastoralism. This study used the social-ecological systems framework to examine how pastoral mobility in the semi-arid, montane communal rangeland in South Africa adapted to the changing socio-political landscape. It analysed the impact of apartheid and democratic era legislation and policies over the past 70 years. Apartheid legislation promoted betterment planning and the privatisation of communal lands by awarding access to most of the grazing areas to a few wealthier pastoralists. This led to increased stocking densities and further restriction of herd mobility when the majority of herds were restricted to fewer grazing camps. Democratic era land reform policies continue to advocate for the modernisation and sedentarisation of pastoral practices. The persistence of mobility among livestock keepers despite discriminatory policy interventions suggests that this is a particularly resilient and necessary element of their practices. We argue that agricultural legislation and policies regarding livestock farming should promote landscape connectivity to allow mobile pastoralists to access variable resources. Connected landscapes should be viewed as alternative ways to modernising pastoralism and these should prevent elite capture when the land is subdivided.